NaIO4-mediated C-H activation of alkylbenzenes and alkanes with LiBr - Shaikh, T. M.; Sudalai, A. (Tetrahedron Letters, 2005)
NaIO4 oxidizes lithium bromide efficiently under acidic conditions to functionalize alkylbenzenes and alkanes and produce the corresponding bromo and acetoxy derivatives in excellent yields. The protocol also demonstrates the direct conversion of cyclohexane into trans-1,2-dibromocyclohexane in moderate yield. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: alkanes; alkylbenzenes; C-H activation; Lithium bromide; NaIO4

NalO(4)/LiBr-mediated diastereoselective dihydroxylation of olefins: a catalytic approach to the prevost-woodward reaction - Emmanuvel, Lourdusamy; Shaikh, T. M. A.; Sudalai, A. (Organic Letters, 2005)
LlBr catalyzes efficiently the dihydroxylation of alkenes to afford syn and anti diols with excellent diastereoselectivity depending upon the use of NaIO4 (30 mol %) or Phl(OAc)(2) (1 equiv), respectively, as the oxidants. The oxidation of non-benzylic halides has been achieved for the first time to afford the corresponding diols in excellent yields.

NBS-catalyzed hydroamination and hydroalkoxylation of activated styrenes - Talluri, S. K.; Sudalai, A. (Organic Letters, 2005)
N-Bromosuccinimide efficiently catalyzes the hydroamination and hydroalkoxylation of activated styrenes using tosylamides, carbamates, and alcohols as the nucleophiles to afford amino and ether derivatives, respectively. Both the processes give good to excellent yields of the products with 100% regioselectivity (Markovnikov fashion).

Natural kaolinitic clay: a remarkable catalyst for highly regioselective chlorination of arenes with Cl-2 or SO2Cl2 - Jayachandran, B.; Phukan, P.; Daniel, Thomas; Sudalai, A. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2006)
Natural kaolinitic clay containing transition metals such as Fe and Ti in its lattice has been found to exhibit unusual regioselectivity in the liquid-phase chlorination of arenes with either Cl-2 or SO2Cl2 as the chlorinating agent para-Chlorinated products are predominant for most of the substrates with an exceptional case of ortho-selectivity for the chlorination of aniline.
Keywords: Aniline; chlorination; chlorine; ortho-chloroaniline; sulfuryl chloride